Secondary metabolite induced tolerance to Fusarium oxysporum f.sp. cubense TR4 in banana cv. Grand Naine through in vitro bio-immunization: a prospective research translation from induction to field tolerance - Damodaran, T; Mishra, Maneesh; Muthukumar, M; Rajan, Shailendra; Yadav, Kavita; Kumar, Alok; Debnath, Prasenjit; Kumari, Sangeeta; Bora, Popy; Gopal, Ram; Kumar, Sandeep (Frontiers in Microbiology, 2023)
An innovative tissue culture mediated incorporation of metabolite-based biomolecule (Bioimmune) at in vitro stage itself in banana cv. Grand Naine was developed and validated for the production of Fusarium oxysporum f.sp. cubense TR4 tolerant plantlets. The novel bio-immune formulation developed by us, exhibited a significant antifungal potency against Foc TR4 with a highest percent inhibition (100%) at a 2.5% concentration of bio-immune on the 5 th , 7 th , and 9 th DAI. Bio-immune integrated during in vitro shoot proliferation stage in banana cv. Grand Naine recorded significant enhancement in the growth of roots and shoots. Bio-immune (0.5%) fortified media produced 12.67 shoots per clump whereas control registered only 9.67 shoots per clump.Similarly, maximum root numbers (7.67) were observed in bio-immune plants which were significantly higher over control (5.0). The bio-immunized banana transplants recorded a higher survival rate (97.57%) during acclimatization as compared to the control (94.53%). Furthermore, evaluation of the bio-immunized plants in pot experiments revealed that unimmunized plants treated with FocTR4 (TF) exhibited mortality between 60 and 90 days. On the 90 th day after planting, a high mean disease severity index (DSI) of 3.45 was observed with unimmunized plantlets while the bio-immunized plants (TFBI) and ICAR-FUSICONT treated plants (TFTR) showed substantially reduced DSI (0.20 and 1.00) compared to FocTR4 treated control (TF).Significant increase in polyphenol oxidase (PPO), peroxidase (POD), β-1,3-glucanase, phenylalanine ammonia-lyase (PAL), chitinase activities, and enhanced phenol contents were recorded in bio-immunized plants compared to unimmunized plants. Field experiments at two different locations in Bihar, India revealed that bunch weight, no. of hand/bunch, and no. of finger/hand of bio-immune treated plants were significantly higher compared to the control.